Pengaruh Ukuran Dewan, Karakter Eksekutif dan Faktor Lainnya terhadap Penghindaran Pajak - Cindy Junisaviolika Hernandi; Hilary Flora A. T. Lasar (Media Bisnis, 2025)
The purpose of this study is to analyze factors that can influence tax avoidance in manufacturing companies. This study uses seven independent variables: CEO narcissism, board of commissioners size, female directors, financial distress, company size, return on assets, and executive character. The sample used in this study consists of 217 sample data from 74 manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the period from 2021 to 2023. The method used in this study is purposive sampling. To analyze the data, this study uses multiple regression. This study found that the independent variable of financial distress has a positive effect and return on assets (ROA) has a negative effect on tax avoidance. While CEO narcissism, board size, female directors, company size and executive character do not affect tax avoidance.